Literature review on fundamental concepts and definitions, objectives and policy goals as well as instruments relevant for socio-ecological transition - Anna Dimitrova; Katarina Hollan; Daphne Laster; Andreas Reinstaller; Margit Schratzenstaller; Ewald Walterskirchen; Teresa Weiss (WWWforEurope, 2013)
The research project WWWforEurope undertakes to lie the theoretical and empirical foundations for the embarkment on a new socio-ecological growth path in Europe. The new path underlines the need to guarantee Welfare as a broad universal principle for its population, assuring economic and social prosperity. The new path stresses the value of achieving – what we call – Wealth, a value in which material and immaterial resources are combined with the goal to enrich people`s lives and to preserve natural resources, nature and bio-diversity. Both cannot be achieved without Work: Europe needs to enable its population to achieve their life satisfaction at the highest level possible and Work is one of the most – if not, the most – fundamental precondition for this. In short, the overarching question the WWWforEurope project attempts to answer is what kind of new European growth and development strategy is necessary and feasible, enabling a socio-ecological transition to high levels of employment, well-being of its citizens, social inclusion, resilience of ecological systems and a significant contribution to the global common goods like climate stability. Thus the project's central goals are to identify the forces and challenges necessitating deliberations on a new growth path, to define socio-ecological transition, key actors and main obstacles, and to find out how the process of a socio-ecological transition can be initiated, monitored, and accelerated on an institutional level (EU, national and regional level). A central prerequisite to successfully accomplish these central goals is to establish a common understanding of the central questions raised by this undertaking and to create awareness for the project's systemic and interdisciplinary approach. To this behalf, this paper presents fundamental concepts, terms and definitions relevant for socio-ecological transition. Hereby the paper focuses on the concepts of sustainability, growth, innovation, welfare and well-being, wealth and work. We also look at the various dimensions and definitions of transition/transformation which can be found in the literature, trying to concretise the concept of a socio-ecological transition forming the context and starting point of the WWWforEurope project. The necessity to accomplish a socio-ecological transition represents the starting point and the background against which the concepts and terms addressed in this paper gain their relevance. Economic, environmental and social sustainability and sustainable growth and development, respectively, are the central and final aim of the envisaged socio-ecological transition. Sustainability is an indispensable precondition for societal and individual welfare/well-being. Socio-ecological transition to achieve sustainability requires putting into question the prevailing view on economic growth. While economic growth may help to reduce poverty or unemployment and may thus be positively related with social sustainability, this often implies negative external effects for the environment. Alternative growth concepts are to be explored therefore, which do not consider the economic dimension of sustainability only, but explicitly try to incorporate social and environmental aspects in addition. Several more sustainability-oriented growth concepts have been brought into the discussion more recently. All of them are departing from the empirical fact that with increasing levels of GDP per capita the relation between economic growth and societal as well as individual well-being is weakening and that economic growth on the contrary may even endanger environmental and social sustainability (e.g. due to too little time for family and friends) and thus negatively affect quality of life and well-being. A more sustainable perspective on growth requires a more sustainable view on innovation, as a central driver for growth. Within the context of a socio-ecological transition based on sustainable growth, ecological and social innovation gain in importance vis-à-vis purely profit-oriented innovation. Long-term growth is based on wealth as the productive base of an economy. Sustainable growth and development needs to rest on a comprehensive/inclusive wealth concept taking into account, besides the conventional material assets, also natural capital. Finally, socio-ecological transition will also affect the organisation of work/labour. This paper tries to define and concretise these fundamental concepts and terms. Thus it should provide some kind of lexicon, which serves as starting point and background for the work on the central questions guiding the WWWforEurope project. Wherever possible, the paper should facilitate the agreement on common definitions. It is not the aim of the paper to elaborate tradeoffs in depth and to offer solutions and answers already. It rather strives to motivate all research groups involved in the WWWforEurope project to use and discuss the existing concepts, may they be consistent or just offer a variety of thought. It also attempts at drawing attention to the existence of trade-offs and open questions relevant for the various research areas. Moreover, the paper wants to inspire the search for best (or the identification of not working) practices, and it wants to increase the awareness for existing barriers to change. While the paper is not able to elaborate in depth distributional and gender aspects as crucial cross-cutting issues, it aims at directing attention at them and at inspiring research undertaken in the WWWforEurope project to consider these cross-cutting issues. Finally, the paper does not focus too much on policy issues. It is the aim of the overall project to identify (potential) interlinkages, trade-offs and synergies and to discuss policy options and instruments in details to support a more dynamic, inclusive and ecological growth and development path for Europe.
Keywords: D6; E02; E61; H11; H51; H52; H53; H54; H55; I31; J11; J16; L16; O31; O43; O44; R11; Q20; Q40; Q50; Q51; Q58; 330; Behavioural economics; beyond GDP; biophysical constraints; ecological innovation; economic growth path; gender; innovation; social innovation; socio-ecological transition; sustainable growth; synergies; wealth